Towards Cognitive Communication and Other Applications of Cognitive Computing - Williams, Andy (My University, 2020)
The term cognitive communications has been used to describe “human-centric” communication systems that adapt to different behaviors, expectations and preferences. This paper explores a more general use of the term by attempting to enumerate all communication functions that might benefit through being executed by systems of individual or collective cognition. Systems of individual cognition might be represented by intelligent agents (based on some subset of the functionality suggested to be required for Artificial General Intelligence) with the capacity to change any property of communication. Communication functions executed by such systems optimize individual outcomes. Systems of collective cognition might be represented by collective intelligence solutions (based on some subset of functionality suggested to be required for General Collective Intelligence) with the capacity to enable such intelligent agents to self-assemble into communication networks using any combination of network topology, protocols, spectrum or other properties. Communication functions executed by such systems optimize collective outcomes. From this perspective, cognitive communication is explored as a specific case that might be generalized to apply to any number of other sectors, such as cognitive power generation and distribution, cognitive agriculture, cognitive healthcare, etc.
Keywords: Artificial General Intelligence; cognitive communication systems; cognitive computing; General Collective Intelligence; intelligent agent